Hubungan Kualitas Produk, Harga, dan Lokasi Terhadap Kepuasan Pelanggan pada Toko Rifki Busana Dalam Rangka Pemasaran Online - Safri Safri; Iswandir Iswandir (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2018)
Based on data processing using SPSS 22, obtained multiple correlation coefficient (R) = 0.972, so there is a strong or positive relationship between Product Quality, Price and Location on Customer Satisfaction at Rifki Busana Store, Jakarta, Determination Coefficient (R2) = 97,2% so that 2,8% is influenced by other factors not examined in this study. To obtain multiple regression values Y = 3.828 + 0.387X1 + 0.335X2 + 0.486X3 and for the t test with a level of confidence Î± = 5% obtained t value of 1.692 so that there is a significant positive effect between variables X1 to Y, and that there is a significant positive Significantly between variables X2 to Y, and there is a significant positive effect between variables X3 to Y, Ho is rejected and Ha is accepted, which means there is an influence of Product Quality, Price, and Location on the Customer. Satisfaction. As well as for the F-test with a level of confidence Î± = 5%, the F value is obtained from 0,000 which is smaller than the trust value which means that the variables X1, X2, X3 together have a significant effect on variables equal to Y. Therefore, it can be concluded that the model the regression used in this study is valid Keywords: Product Quality, Price, Location, Customer satisfaction